O trabalho análogo à escravidão no Brasil a luz das metas 8.7 e 8.8 dos objetivos do desenvolvimento sustentável: Sergipe em foco - Ribeiro, Ayala Pontes Amaral (2021)
Precarious work, which ranges from forced labor, child labor and even slavery, is an obstacle to sustainable development, since there is no way to reach its fullness without ensuring that labor relations are healthy and balanced. Given the relevance of the topic, in the national and international scenario, in 2015 the 2030 Agenda was established, with Brazil being a signatory of the document, which points out seventeen sustainable development goals that permeate themes from the most diverse areas, ranging from climate conditions to eradication of poverty. Our work focuses on objective number eight, which deals with Decent Work and Economic Growth, with a focus on targets numbers 8.7 and 8.8, focusing on immediate and effective measures to eradicate forced labor, end modern slavery and still protect labor rights and promote safe and secure working environments for all workers and people in precarious employment. Thus, the objective of this research is to analyze the implications of work analogous to slavery in Brazil and Sergipe in achieving the goals of nº 8.7 and 8.8 of Agenda 2030. The methodological procedures consisted of bibliographical research and documental analysis that were collected in the databases of the Ministry of Economy, SIT, Smartlab, and National Employment System-SINE; and also by the Brazilian Institute of Geography and Statistics (IBGE).The results show that work analogous to slavery is still a reality on Brazilian soil, with a greater incidence in the North and Northeast regions of the country, especially in the States of Pará and Maranhão. They are mostly linked to the agribusiness sector, such as: logging and livestock. With regard to the State of Sergipe, the research found the (in)existence of work in conditions similar to slavery in Sergipe soil, since, in the control bodies of this type of work, SIT and Smartlab, there are no records of this information. However, since these activities are not cataloged, we cannot conclude that they do not exist, as shown in this research, given that in the Labor Court in Sergipe, there is a case, with a conviction, due to the practice of economic activity exploited by slave labor, despite the absence of a database in the instances responsible for controlling this type of work. The research contributes to science in approaching the theme, since the issue of precarious work and slavery-like work is analyzed from the perspective of the 2030 agenda of the UN Sustainable Development Goals. It also contributes with information that can serve institutions that protect labor and employment relations in Brazil, as well as public policies aimed at eradicating degrading work in Sergipe and in Brazil.